THE MANAGERIAL FUNCTION OF THE MADRASAH HEAD IN CREATING AN EFFECTIVE MADRASAH - Munawir; Dewiyanti; Mansur (UNISAN JURNAL, 2024)
The managerial ability of the Madrasah head is an important and strategic factor in the framework of improving the quality and progress of the Madrasah he leads. With managerial skills, it is hoped that the Madrasah head can make the Madrasah lead into an effective Madrasah. In an effective Madrasah, the Madrasah head has a strong role in planning, organizing, directing and controlling. The results of the research are: 1) The managerial ability of the Madrasah head in planning to create an effective Madrasah in accordance with the criteria for an effective Madrasah, The managerial ability of the Madrasah head in organizing an effective Madrasah according to procedures, 2 ) The managerial ability of the Madrasah in directing the creation of an effective Madrasah has also gone well., Managerial ability Control or supervision carried out by the Madrasah head in creating an effective Madrasah by carrying out monitoring and evaluation. From the overall managerial management of Madrasah heads, it can be stated that the Madrasah head at Madrasah Tsanawiyah Darul Ishlah NW, Angsana District, Tanah Bumbu Regency has been able to create an effective Madrasah because he has implemented effective Madrasah indicators which refer to input, process, output and outcome.